PENEGAKAN HUKUM TERHADAP PELAKU PERZINAHAN DALAM PERSPEKTIF KUHP DAN QANUN DI LHOKSUKON ACEH UTARA - Simon Purba; Mustamam Mustamam; Adil Akhyar (Jurnal Ilmiah METADATA, 2021)
Adultery in Islamic law is considered a very condemnable act and is considered a finger. The problems in this discussion are how to regulate the crime of adultery according to the Criminal Code, how to commit adultery according to Qanun Number 6 of 2014 concerning Jinayat Law, how to compare the crime of adultery according to the Criminal Code and Qanun Number 6 of 2014 2014 Regarding Jinayat Law. This study uses a descriptive method through a normative approach (legal research), namely an approach to problems, carried out by examining various legal aspects in terms of applicable regulations. The results of the study show that the crime of adultery as regulated in Article 284 of the Criminal Code is sentenced to imprisonment for a maximum of nine months. Adultery has existed since ancient times, there are differences of opinion regarding the crime of adultery regarding whether or not it is necessary to be seen as an act that is prohibited and can be threatened with punishment. In Dutch terminology adultery is called overspel. The crime of adultery in Islamic Shari'a is the most indecent act which illustrates how the common sense of the perpetrator does not work at all. In fact, Allah S.W.T has provided a lawful way through a marriage. Adultery is an ulcer that not only harms oneself but also others and the environment. While Qanun number 6 of 2014 concerning the law of jinayat is contained in Article 33 which explains that every person intentionally commits, every person repeats an act, every person or business entity intentionally provides facilities/promotes adultery, adultery with children, adultery with mahram. Comparison of the crime of adultery according to positive law and Qanun number 6 of 2014 concerning the law of jinayat, the elements of the criminal act of adultery and sanctions as well as the procedures for applying the law to the perpetrators of the crime of adultery are contained in Article 284 of the Criminal Code. While Qanun number 6 of 2014 concerning the law of jinayat is contained in Article 33 paragraph (1) Everyone who intentionally commits Zina, is threatened with 'Uqubat Hudud' 100 lashes. Paragraph (2) Everyone who repeats the act as referred to in paragraph (1) is threatened with 'Uqubat Hudud lashes 100 (one hundred) times and can be added with 'Uqubat Ta'zir a fine of a maximum of 120 (one hundred and twenty) grams of pure gold or 'Uqubat Ta'zir' Uqubat Ta'zir imprisonment for a maximum of 12 (twelve) months.